Performance Comparison of a Rhodamine B Concentration Sensor in Distilled Water Using a Fiber Coupler and Fiber Bundle as a Probe without Direct Contact with the Sample - Samian Samian; Supadi Supadi; Alifiah Qodartin Nisa Budiharjo; Patricia Patricia; Mirna Putri Anggraeni (Universitas Negeri Malang, 2022)
Detection of the concentration of rhodamine B in distilled water using a fiber coupler and fiber bundle as probes with a static position on the sample surface and not in direct contact with the sample was successfully carried out. The working mechanism of the sensor uses the principle of sample absorption of the light that passes through it. The concave mirror functions as a reflector and a sample container, allowing an undirect contact probe sensor with the sample. Both types of sensors show similar performance. The best detection is shown by sensors that use fiber bundles as probes. The resulting sensitivity and resolution are 2.1 mV/ppm and 0.29 ppm, respectively.DOI: 10.17977/um024v7i22022p127